Domestic politics and the reorientation of the look east policy in the era of President Ebrahim Raisi - Asep Kamaluddin Nashir; Rizky Hikmawan (Journal of Law, Administration, and Social Science, 2026)
This article analyzes the formation of Iran’s Look East Policy under the presidency of Ebrahim Raisi by positioning domestic politics as the primary explanatory variable. Departing from approaches that interpret the policy as a reactive response to Western pressure and international sanctions, the article argues that Look East Policy constitutes a structurally produced domestic political outcome. The study employs a layered analytical framework combining ideational power and the bureaucratic politics model within the tradition of Foreign Policy Analysis (FPA), using qualitative library-based research methods. The findings show that the ideological structure constructed by the Supreme Leader shapes the foreign policy legitimacy space (policy space), which is subsequently translated into institutional preferences and consolidated through bureaucratic interactions among the president, the Ministry of Foreign Affairs, and the IRGC. This process produces elite consensus that is crystallized through policy formulation, transforming Look East Policy into an official strategic orientation and institutionalizing it through bilateral relations, non-Western multilateralism, and sectoral cooperation. The article concludes that Look East Policy is a policy ideologically conditioned, bureaucratically produced, and institutionally embedded, in which Western external pressure functions as a triggering context, while domestic political structures determine the direction and character of Iran’s foreign policy.